A comparison of recreational water illness awareness and frequency of swimming - Chan, Elden; BCIT School of Health Sciences, Environmental Health; MacLeod, Martin (BCIT Environmental Public Health Journal, 2014)
Objective: Swimming pools have potential to create health hazards that range from physical, chemical to biological. Biological concerns center on communicable diseases which can be spread through poor hygiene practices. To prevent the spread of disease, swimmers must be informed and practice appropriate hygiene. This study aims to determine whether the frequency of swimming had an influence on swimming pool hygiene knowledge. Method: Survey questions focusing on risk factors for communicable disease spread, and personal hygiene practices were developed using the pool operation handbooks, input from environmental health instructors at the British Columbia Institute of Technology, as well as past surveys from other studies. Pool patrons were surveyed at Hillcrest Community Centre in Vancouver. Scores from these tests were then analyzed in NCSS9 using one-way ANOVA tests and Two-Sample t-tests. Results: 167 validated surveys were analyzed. The most often incorrectly answered questions were in regards to the duration of avoiding swimming after diarrheal illness, pre-swim hygiene, and after bathroom use hygiene. No statistically significant difference in mean test score was found in individuals that swam more than once a week, more than once a month, or less than once a month. Statistically significant differences in mean test scores were found for individuals that read signs, and age group. Conclusion: From the data, it is observed that those who swam more frequently were not more informed on pool hygiene issues than those who swam less. The sample size (n=167) for this conclusion may be too small, since beta value was 87.5%.